New approaches to the treatment of patients with arterial hypertension with comorbid pathology living in the environmental conditions of the south of Western Siberia - Yu. A. Nikolaev; V. Ya. Polyakov; M. G. Magomedov; E. V. Sevostyanova (Юг России: экология, развитие, 2021)
Aim. The aim of the study was to study the effectiveness of complex treatment of arterial hypertension comorbid with dorsopathy depending on the severity of atherosclerotic lesions of the carotid arteries.Material and Methods. The object of the study were 80 patients with arterial hypertension comorbid with dorsopathy, admitted for examination and treatment at the clinic of Federal Research Centre of Fundamental and Translational Medicine (FRC FTM.) in Novosibirsk. Patients were men and women aged 18 to 75 years. They underwent clinical, laboratory and functional examination in the inpatient facility of the FRC FTM. Assessment of the degree of atherosclerotic lesions of the carotid arteries was carried out using ultrasound duplex scanning of arteries.Results. It was found that in patients with hypertension combined with dorsopathy and atherosclerotic lesions of the carotid arteries without hemodynamically significant stenosis and signs of instability of atherosclerotic plaques, complex treatment with the use of SMT therapy or magnetotherapy more effectively reduces systolic blood pressure than treatment without hardware physiotherapy and more quickly stabilises blood pressure on targets.Conclusion. In patients with hypertension accounting for the presence of comorbidities in the form of dorsopathy of the cervical spine and atherosclerosis of the carotid arteries that allows the personalization of the therapy of such patients using methods of physiotherapy, reducing the time to achieve the therapeutic effect improved the quality of life of patients.